The Missing Structures of Pasteur’s Aspartates - Damian J. C. Kersten; Martin Lutz (Crystals, 2025)
In his crystallographic research on chiral separation, Louis Pasteur reported the crystals of the sodium salts of enantiopure and racemic aspartic acid. Their atomic structure remained unknown to this day. In the present article, the two crystal structures are reported. The X-ray diffraction of both crystals was severely affected by twinning. Their crystal packing is very similar and can be described as a three-dimensional coordination network. A decomposition of the structures into layers helps to explain the twinning as stacking faults. In the enantiopure crystal, the layers are parallel to <semantics>(0,1,0)</semantics> and in the racemic crystal parallel to <semantics>(0,0,1)</semantics>. The sum formula of the two crystal structures is identical, representing the monohydrate of the monosodium aspartate.